2017
DOI: 10.15406/japlr.2017.06.00186
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Analysis of Amino Acid and Antioxidant Composition of Three Medicinal Plants of (Pithoragarh) Uttarakhand Himalayas

Abstract: Antioxidant phytochemicals such as vitamin C, β-carotene, lutein, α-tocopherol, amino acid and total phenolics, were estimated in some medicinal plants using a reverse phase HPLC system. Wild plants play a vital role in the health security of Himalayan inhabitants and constitute significantly to their diet. Amino acid was analysis performed using the Waters Associates PICO-TAG method. The total amino acid content in P. indica was 58.80mg amino acid/g sample (dry weight), E. thymifolia was 123.92mg amino acid/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
5
2
Order By: Relevance
“…The total amino acid contents were 58.80 mg g −1 DW in P. indica, 123.92 mg g −1 DW in E. thymifolia and 225.73 mg g −1 DW in P. hirta. The ratios of essential amino acids to total amino acids were 0.57, 0.47 and 0.65, respectively [52]. Although in our study the leaf extract was richer in amino acids, the ratio of essential to total amino acids was 0.37, whereas in the twig extract it was 0.55.…”
Section: Discussioncontrasting
confidence: 61%
“…The total amino acid contents were 58.80 mg g −1 DW in P. indica, 123.92 mg g −1 DW in E. thymifolia and 225.73 mg g −1 DW in P. hirta. The ratios of essential amino acids to total amino acids were 0.57, 0.47 and 0.65, respectively [52]. Although in our study the leaf extract was richer in amino acids, the ratio of essential to total amino acids was 0.37, whereas in the twig extract it was 0.55.…”
Section: Discussioncontrasting
confidence: 61%
“…In another study, Guzelsoy et al (2017) reported that some wild edible plants collected from three different biogeographic of Turkey are rich in vitamin C, ranging from 2.0 to 129.4 mg 100g -1 . Prasad and Chandra (2018) also reported similar values of ascorbic acid in some wild edible medicinal herbs as P. hirta (108.40 mg 100g -1 ), E. thymifolia (88.48 mg 100g -1 ), and P. indica (77.49 mg 100g -1 ). According to the results, the daily vitamin C requirement of an adult person can be provided by consuming both the T. orientalis and T. reticulatus.…”
Section: Variation Of Bioactive Compounds İn the Nine Examined Speciesmentioning
confidence: 60%
“…Similarly, in a study carried out by Moran-Palacio et al (2014), some medicinal species used in traditional medicine were found to be very rich in amino acids. Prasad and Chandra (2018) showed that the total essential amino acid levels were ranging between 35.58 mg 100g -1 and 145.82 mg 100g -1 , and the amount of total amino acid content of Pavetta indica was 58.80 mg 100g -1 , E. thymifolia 123.92 mg g -1 , and P. hirta 225.73 mg 100g -1 .…”
Section: Variation Of Bioactive Compounds İn the Nine Examined Speciesmentioning
confidence: 99%
“…14 And that the medicinal plants (dry) leaves. Euphorbia thymifolia only contains 0.14 g/100g of lysine, Zinziber officinale 0.14 g/100g and Pavetta indica 0,30 g/100 g 15 And for Vernonia amygdalina 0.05 g/100g.were found. All values lower than for Artemisia.…”
Section: The Unsuspected Role Of Amino Acidsmentioning
confidence: 93%